Mutagenesis of the promoter of the oil palm homogentisate geranylgeranyl transferase gene (HGGT) by PCR-driven overlap extension - Karim, Mohd Shahrul Nizwanshah; Abdullah, Siti Nor Akmar (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
PCR-driven overlap extension is a simple and versatile tool in performing site-directed mutagenesis. This technique contains two stages of PCR. The first stage is the initial PCR to generate mutated gene segments that overlapped, which are then used as a DNA template in the second stage PCR to produce full length product with the site-directed mutation. The internal primer serves to introduce nucleotide substitution for site-directed mutagenesis by complementary 3’ ends on the intermediate segments. The full-length product amplied by the flanking primers in the second stage PCR includes the restriction enzyme sites for inserting the product into an expression vector for cloning purposes.